PROBLEMS OF FEMALE STUDENTS IN LEARNING PROGRAMMING SUBJECTS (Intent Research Scientific Journal, 2023)
In recent years, there has been a growing push for diversity and inclusion in the field of computer science and programming. Despite these efforts, the gender gap in tech-related fields remains a significant issue. Female students continue to encounter unique challenges in their pursuit of learning programming subjects. This article aims to shed light on some of the problems that female students commonly face in this male-dominated field.